Youtube Vlogging: Promoting Self-Regulation in Public Speaking - Khabib, Samsul (JET ADI BUANA, 2019)
Abstract: This paper explored the use of YouTube video blogging (vlogging) to promote self-regulation in an English for Public Speaking class. The self-regulation includes four essential components namely planning, monitoring the plans, controlling and changing the plans, and reflecting on the works. Furthermore, the investigation was to determine what self-regulation improvement has developed through YouTube vlogging and how YouTube vlogging can improve students’ self-regulation. The research method was a Classroom Action Research. To obtain the data, Self-Regulation Questionnaires in the Pre-Survey and Post-Survey, students’ journal entries and semi-structured interviews were employed as the instruments. Then, the data were analyzed using Quantitative and Qualitative approaches. The data analysis results show that participants improve their self-regulation. The improvement can be seen from the results of the Post-Survey compared to Pre-Survey and the second students’ journal entries compared to the first students’ journal entries. Furthermore, the results of semi-structured interviews reveal that the improvement was caused by the process of YouTube vlogging creation.